2020
DOI: 10.1021/acs.langmuir.0c01939
|View full text |Cite|
|
Sign up to set email alerts
|

Stress or Strain Does Not Impact Sorption in Stiff Mesoporous Materials

Abstract: The present paper investigates strain-induced sorption in mesoporous silicon. Contrarily to a previous report based on indirect evidence, we find that external mechanical strain or stress has no measurable impact on sorption isotherms, down to a relative accuracy of 10 −3 . This conclusion is in agreement with the analysis of the sorption-induced strain of porous silicon and holds for other stiff mesoporous materials such as porous silicas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…While the simplest explanation is the existence of connections between neighboring pores, another possibility, put forward by Grosman and Ortega, 35 would be an indirect mechanical coupling. However, in view of our recent experiments on strain-and stress-induced adsorption, 19 this mechanical coupling is negligible. Moreover, the existence of connections between pores is also suggested by the moderate anisotropy of the diffusion constant measured by NMR.…”
Section: ■ Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…While the simplest explanation is the existence of connections between neighboring pores, another possibility, put forward by Grosman and Ortega, 35 would be an indirect mechanical coupling. However, in view of our recent experiments on strain-and stress-induced adsorption, 19 this mechanical coupling is negligible. Moreover, the existence of connections between pores is also suggested by the moderate anisotropy of the diffusion constant measured by NMR.…”
Section: ■ Discussionmentioning
confidence: 87%
“…For instance, as shown in Figure 1, the evaporation pressure increases with the pore length l. This can be explained by an increase in the diameter of the interconnections with the etching time, a reasonable hypothesis in view of an earlier work where we observed that the isotherms change with the etching time. 19 In this picture, the observation in the same samples of a small cavitation event (about 1% of the total volume for the 20 μm/70% sample at 77 K) implies that some pores or some sections of the pores are connected to their neighbors only through some very narrow constrictions.…”
Section: ■ Discussionmentioning
confidence: 91%
See 3 more Smart Citations